EFFECTS OF PHOSPHATED TITANIUM AND ENAMEL MATRIX DERIVATIVES ON OSTEOBLAST BEHAVIOR IN VITRO - Dacy, J. Anthony (2007)
PURPOSE: The purpose of this study was to evaluate the effects of phosphated titanium and EMD on osteoblast function. MATERIALS AND METHODS: Primary rat osteoblasts were cultured on discs of either phosphated or non-phosphated titanium and in half of the samples 180μg of EMD was immediately added. Media was changed every 2 days for 28 days, and then analyzed by TGF-β1 and IL-1β ELISAs. Scanning electron microscopy (SEM) and light microscopy (LM) was used to evaluate nodule formation and mineralization. RESULTS: Microscopic evaluation revealed no differences in osteoblast attachment on all discs, regardless of treatment. Osteoblast nodule formation was observed in all groups. In the absence of mineralizing media, nodules on the non-phosphated titanium samples showed no evidence of mineralization. All nodules on the phosphated titanium had evidence of mineralization. ELISA analysis revealed no significant differences in IL-1β production between any of the groups. The EMD treated osteoblasts produced significantly more TGF-β1 than non-EMD treated cells for up to 8 days, and osteoblasts on phosphated titanium produced significantly more Tgf-ß1 at 8 days. DISCUSSION AND CONCLUSION: Osteoblast attachment appeared unaffected by surface treatment. EMD initiated early TGF-β1 production, but production decreased to control levels within 10 days. Phosphated titanium increased Tgf-ß1 production at 8 days, and induced nodule mineralization even in the absence of mineralizing medium.